High-efficiency low-energy-consumption spheroidizing annealing process of weathering resistant steel BNH8 for high-strength bolt
By adding graphene to the melt of weathering steel BNH8 and performing ultrasonic treatment, the problems of high energy consumption and unsatisfactory structure of the traditional spheroidized annealing process are solved, and the spheroidized annealing process with high efficiency and low energy consumption is realized, which improves the bolts Strength and toughness.
Patent Information
- Application Number
- CN202411331075.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-17
AI Technical Summary
The traditional spherical annealing process has a high energy consumption for weather-resistant steel BNH8 for high-strength bolts and its structural structure is not ideal, which affects its performance.
Add graphene to the melt of weather-resistant steel BNH8 for high-strength bolts and perform ultrasonic treatment, followed by spheroidization annealing, and promote carbon atom diffusion and carbide formation through the layered structure of nanographene and the cavitation effect of ultrasonic treatment. , improve the spherical annealing effect and reduce energy consumption.
It significantly improves the efficiency and performance of the spheroidized annealing process, reduces energy consumption, and improves the strength and toughness of the material to form a more uniform carbide structure.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of spheroidizing annealing, and in particular to a high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts. Background Art
[0002] Metal heat treatment is a process of heating a metal workpiece to a suitable temperature in a certain medium, keeping it at this temperature for a certain period of time, and then cooling it at different speeds in different media to control its performance by changing the surface or internal microstructure of the metal material; among them, spheroidizing annealing is an annealing method only applied to steel. The steel is heated to 20~30℃ above Ac1, kept warm for a period of time, and then slowly cooled to a temperature slightly lower than Ar1 and kept for a period of time. The purpose is to make the lamellar cementite and proeutectoid cementite in the pearlite become spheroidal and evenly distributed in the ferrite matrix. Medium carbon steel and high carbon steel with this structure have low hardness, good machinability and high cold deformation ability.
[0003] Weathering steel BNH8 for high-strength bolts is a high-quality alloy for cold heading. Generally speaking, most of all spheroidizing activities performed on high-quality alloy steel bars are to improve the cold formability of the steel. The spheroidized microstructure is ideal for cold forming because it reduces the flow stress of the material. Steel can be spheroidized to produce a spheroidal carbide structure in a ferrite matrix. Traditional annealing is a complete annealing, generally using 920℃ for a certain period of time. The resulting organization is a lamellar organization. Although normal production can meet the standard requirements, the energy consumption required is very high due to the high insulation temperature, long time and great energy waste during the annealing process. Summary of the invention
[0004] The object of the present invention is to provide a high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts, wherein graphene is added to the weathering steel BNH8 for high-strength bolts, the steel is treated with ultrasound, and then spheroidizing annealing is performed.
[0006] Furthermore, the weathering steel BNH8 for high-strength bolts is in a molten state before solidification.
[0007] Furthermore, the high-efficiency and low-energy consumption spheroidizing annealing process of the weathering steel BNH8 for high-strength bolts comprises the following steps: (1) Graphene with a mass of 0.05 to 0.1 times that of the melt of high-strength weathering steel BNH8 for bolts was added to the melt, stirred at 200 to 300 r / min for 10 to 15 min, and then subjected to ultrasonic treatment until solidification to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; (2) The high-strength bolt weathering steel BNH8 loaded with graphene is initially annealed, and then water quenched to room temperature to obtain the high-strength bolt weathering steel BNH8 after initial annealing; (3) The high-strength bolt weathering steel BNH8 after initial annealing is heated to 705±10℃, the heating time is controlled to be 3±0.3h, then kept at 705±10℃ for 6~8h, cooled to 500±10℃ with the furnace, the cooling time is controlled to be 8±0.2h, and then air-cooled to below 120℃ to complete spheroidizing annealing.
[0008] Furthermore, the diameter of the graphene in step (1) is 50-80 nm.
[0009] Furthermore, the ultrasonic treatment process in step (1) is to insert an ultrasonic guide rod into the melt to a depth of 10 to 15 mm, and perform ultrasonic treatment until the melt is completely solidified.
[0010] Furthermore, the parameters of the ultrasonic treatment are: ultrasonic treatment power of 300-500W, and ultrasonic frequency of 20kHz.
[0011] Furthermore, the initial annealing process in step (2) is to heat the high-strength bolts loaded with graphene to 1000-1100° C. using weathering steel BNH8, keep the temperature for 10-30 min, and quench with water to room temperature.
[0012] Furthermore, in step (3), the spheroidizing annealing is provided with nitrogen protection, and the flow rate of nitrogen is 10Nm 3 / h.
[0013] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention designs a process of adding graphene to the melt and treating it with ultrasonic waves before the melt of weathering steel BNH8 for high-strength bolts is solidified and formed, and then spheroidizing and annealing the melt, so as to achieve the effect of high efficiency and low energy consumption.
[0014] By adding nanographene to the weathering steel BNH8 melt before solidification, ultrasonic treatment and then spheroidizing annealing are carried out; nanographene has a very high specific surface area and layered structure, and the layered structure can make the carbon atoms in the steel easier to diffuse and spheroidize during spheroidizing annealing. Ultrasonic waves can make the nanographene evenly distributed in the melt, improve the interface bonding force between graphene and steel, and produce cavitation effect to form more nucleation cores in the steel. At the same time, ultrasonic treatment will cause the graphene and carbon atoms in the steel to cross-link to form a larger layered structure, further promoting the formation and spheroidization of carbides in the steel, which can effectively improve the effect of the spheroidizing annealing process and reduce the energy consumption of the spheroidizing annealing process. DETAILED DESCRIPTION
[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0016] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of weathering steel BNH8 using the high-efficiency and low-energy consumption spheroidizing annealing process of high-strength bolt weathering steel BNH8 as follows: Tensile strength: The tensile properties of the embodiments and comparative examples treated by the high-efficiency and low-energy consumption spheroidizing annealing process of high-strength weathering steel BNH8 for bolts were tested in accordance with GB / T 228.1-2010 “Tensile Test Methods for Metallic Materials”.
[0017] Bending strength: The bending properties of the embodiments and comparative examples treated by the high-efficiency and low-energy consumption spheroidizing annealing process of high-strength weathering steel BNH8 for bolts were tested in accordance with GB / T 232-2010 “Methods for bending test of metallic materials”.
[0018] Hardness: The hardness of the embodiment and comparative example treated by the high-efficiency and low-energy consumption spheroidizing annealing process of high-strength bolt weathering steel BNH8 was tested in accordance with GB / T 231.1-2018 "Brinell hardness test of metallic materials Part 1: Test method". Example 1
[0019] A high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts comprises the following steps: (1) Graphene with a diameter of 50 nm and a mass of 0.05 times that of the melt of high-strength weathering steel BNH8 for bolts was added to the melt, stirred at 200 r / min for 10 min, and an ultrasonic guide rod was inserted into the melt with an insertion depth of 10 mm. The ultrasonic treatment power was 300 W and the ultrasonic frequency was 20 kHz. The ultrasonic treatment was performed until the melt was completely solidified to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; (2) The high-strength weathering steel BNH8 for bolts loaded with graphene was heated to 1000°C, kept at this temperature for 10 min, and then quenched with water to room temperature to obtain the high-strength weathering steel BNH8 for bolts after initial annealing treatment; (3) The high-strength bolt weathering steel BNH8 after initial annealing treatment was heated to 705°C, the heating time was controlled to be 3h, then kept at 705°C for 6h, cooled to 500°C with the furnace, the cooling time was controlled to be 8h, and then air-cooled to below 120°C to complete spheroidizing annealing. Nitrogen protection was set throughout the process, and the nitrogen flow rate was 10Nm 3 / h. Example 2
[0020] A high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts comprises the following steps: (1) Graphene with a diameter of 65 nm and a mass of 0.08 times that of the melt of high-strength weathering steel BNH8 for bolts was added to the melt, stirred at 250 r / min for 13 min, and an ultrasonic guide rod was inserted into the melt with an insertion depth of 13 mm. The ultrasonic treatment power was 400 W and the ultrasonic frequency was 20 kHz. The ultrasonic treatment was performed until the melt was completely solidified to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; (2) The high-strength weathering steel BNH8 for bolts loaded with graphene was heated to 1050°C, kept at this temperature for 25 min, and then quenched with water to room temperature to obtain the high-strength weathering steel BNH8 for bolts after initial annealing treatment; (3) The high-strength bolt weathering steel BNH8 after initial annealing treatment was heated to 710℃, the heating time was controlled to be 3.3h, then kept at 710℃ for 6~8h, cooled to 510℃ with the furnace, the cooling time was controlled to be 8.2h, and then air-cooled to below 120℃ to complete spheroidizing annealing. Nitrogen protection was set throughout the process, and the nitrogen flow rate was 10Nm 3 / h. Example 3
[0021] A high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts comprises the following steps: (1) Graphene with a diameter of 80 nm and a mass of 0.1 times that of the melt of high-strength weathering steel BNH8 for bolts was added to the melt, stirred at 300 r / min for 15 min, and an ultrasonic guide rod was inserted into the melt with an insertion depth of 15 mm, an ultrasonic treatment power of 500 W, and an ultrasonic frequency of 20 kHz. The ultrasonic treatment was performed until the melt was completely solidified to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; (2) The high-strength weathering steel BNH8 for bolts loaded with graphene was heated to 1100°C, kept at this temperature for 30 min, and then quenched with water to room temperature to obtain the high-strength weathering steel BNH8 for bolts after initial annealing treatment; (3) The high-strength bolt weathering steel BNH8 after initial annealing treatment was heated to 695°C, the heating time was controlled to be 2.7h, then kept at 695°C for 8h, cooled to 490°C with the furnace, the cooling time was controlled to be 7.8h, and then air-cooled to below 120°C to complete spheroidizing annealing. Nitrogen protection was set throughout the process, and the nitrogen flow rate was 10Nm 3 / h.
[0022] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: inserting an ultrasonic guide rod into a melt of high-strength weathering steel BNH8 for bolts, the insertion depth is 13 mm, the ultrasonic treatment power is 400 W, the ultrasonic frequency is 20 kHz, and ultrasonic treatment is performed until the melt is completely solidified to obtain high-strength weathering steel BNH8 for bolts after ultrasonic treatment; the remaining steps are the same as in Example 2.
[0023] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: adding graphene with a diameter of 65 nm, which is 0.08 times the mass of the melt of high-strength weathering steel BNH8 for bolts, to the melt, stirring at 250 r / min for 13 min, cooling and solidifying to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; the remaining steps are the same as those in Example 2.
[0024] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (1) is omitted, and step (2) is changed to: heating high-strength weathering steel BNH8 for bolts to 1050° C., keeping the temperature for 25 min, and quenching with water to room temperature to obtain high-strength weathering steel BNH8 for bolts after initial annealing treatment; the remaining steps are the same as those in Example 2.
[0025] Effect example Table 1 below shows the performance analysis results of the high-efficiency and low-energy consumption spheroidizing annealing process of the weathering steel BNH8 for high-strength bolts of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.
[0026] Table 1 Tensile strength (MPa) Bending strength (MPa) Hardness (HV) Example 1 569 423 183 Example 2 578 431 191 Example 3 572 428 186 Comparative Example 1 398 319 154 Comparative Example 2 543 367 175 Comparative Example 3 376 302 142 From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that in the present invention, nano-graphene is added before the weathering steel BNH8 melt is solidified and formed. The nano-graphene has a very high specific surface area and a layered structure. The layered structure can make the carbon atoms in the steel easier to diffuse and spheroidize during spheroidizing annealing, and the nano-graphene has excellent mechanical properties, and its strength can reach 130 GPa, which is more than 100 times that of ordinary steel. Adding nanographene to steel can significantly improve the strength and toughness of the material, making it less likely to break when subjected to a greater load; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that ultrasonic treatment can refine the solidification structure of carbon steel, produce a cavitation effect, and form more nucleation cores in the steel; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that ultrasound can make the nanographene evenly distributed in the melt, improve the interfacial bonding force between graphene and steel, and produce a cavitation effect to form more nucleation cores in the steel. At the same time, ultrasonic treatment can cross-link the carbon atoms in the graphene and steel to form a larger layered structure, further promoting the formation and spheroidization of carbides in the steel, which can effectively improve the effect of the spheroidizing annealing process and reduce the energy consumption of the spheroidizing annealing process.
[0027] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A high-efficiency and low-energy consumption spheroidizing annealing process for weathering steel BNH8 for high-strength bolts, characterized in that: The high-efficiency and low-energy consumption spheroidizing annealing process of the weathering steel BNH8 for high-strength bolts is a process of adding graphene to the weathering steel BNH8 for high-strength bolts, treating it with ultrasound, and then spheroidizing annealing.
2. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 1 is characterized in that: The high-strength weathering steel BNH8 for bolts is in a molten state before solidification and forming.
3. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 1 is characterized in that: The following steps are involved: (1) Graphene with a mass of 0.05 to 0.1 times that of the melt of high-strength weathering steel BNH8 for bolts was added to the melt, stirred at 200 to 300 r / min for 10 to 15 min, and then subjected to ultrasonic treatment until solidification to obtain high-strength weathering steel BNH8 for bolts loaded with graphene; (2) The high-strength bolt weathering steel BNH8 loaded with graphene is initially annealed, and then water quenched to room temperature to obtain the high-strength bolt weathering steel BNH8 after initial annealing; (3) The high-strength bolt weathering steel BNH8 after initial annealing is heated to 705±10℃, the heating time is controlled to be 3±0.3h, then kept at 705±10℃ for 6~8h, cooled to 500±10℃ with the furnace, the cooling time is controlled to be 8±0.2h, and then air-cooled to below 120℃ to complete spheroidizing annealing.
4. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 3 is characterized in that: The diameter of the graphene in step (1) is 50-80 nm.
5. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 3 is characterized in that: The ultrasonic treatment process in step (1) is to insert an ultrasonic guide rod into the melt to a depth of 10 to 15 mm, and perform ultrasonic treatment until the melt is completely solidified.
6. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 5 is characterized in that: The parameters of the ultrasonic treatment are as follows: the ultrasonic treatment power is 300-500W and the ultrasonic frequency is 20kHz.
7. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 3 is characterized in that: The initial annealing process in step (2) is to heat the high-strength bolts loaded with graphene to 1000-1100° C. using weathering steel BNH8, keep the temperature for 10-30 minutes, and quench with water to room temperature.
8. The high-efficiency and low-energy consumption spheroidizing annealing process of weathering steel BNH8 for high-strength bolts according to claim 3 is characterized in that: In step (3), the spheroidizing annealing is provided with nitrogen protection, and the flow rate of nitrogen is 10Nm 3 / h.